2013
DOI: 10.1093/hmg/ddt310
|View full text |Cite
|
Sign up to set email alerts
|

Sterol metabolism regulates neuroserpin polymer degradation in the absence of the unfolded protein response in the dementia FENIB

Abstract: Mutants of neuroserpin are retained as polymers within the endoplasmic reticulum (ER) of neurones to cause the autosomal dominant dementia familial encephalopathy with neuroserpin inclusion bodies or FENIB. The cellular consequences are unusual in that the ordered polymers activate the ER overload response (EOR) in the absence of the canonical unfolded protein response. We use both cell lines and Drosophila models to show that the G392E mutant of neuroserpin that forms polymers is degraded by UBE2j1 E2 ligase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
(68 reference statements)
2
23
0
Order By: Relevance
“…For instance, mutations in the neuroserpin protein cause the autosomal dominant dementia familial encephalopathy with neuroserpin inclusion bodies (FENIB) (Roussel et al . ). Miranda et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, mutations in the neuroserpin protein cause the autosomal dominant dementia familial encephalopathy with neuroserpin inclusion bodies (FENIB) (Roussel et al . ). Miranda et al .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, several neurodegenerative disorders are associated with misfolded proteins. For instance, mutations in the neuroserpin protein cause the autosomal dominant dementia familial encephalopathy with neuroserpin inclusion bodies (FENIB) (Roussel et al 2013). Miranda et al found a correlation with the severity of the symptoms (phenotype), the accumulation of the polymers and the type of mutation in a fly model and that a mutant that induces rapid protein polymerization causes an early-onset disease (Miranda et al 2008).…”
Section: ###mentioning
confidence: 99%
“…It is feasible that interinclusion ER chaperone exchange may act to minimize ER heterogeneity, thereby protecting inclusion‐containing cells from ER stress. Further studies are required to test this directly, and also to establish whether the phenomenon described herein is generalizable to other circumstances of ER fragmentation‐for example, in Russell body–expressing plasma cells seen in chronic inflammation and multiple myeloma (38, 39), other serpinopathies such as FENIB (familial encephalopathy with neuroserpin inclusion bodies) (40), and in response to ischemia (41).…”
Section: Discussionmentioning
confidence: 98%
“…The rate of polymerisation correlates with the phenotype observed in FENIB patients, with faster polymerisation being associated with earlier onset of disease [8,9]. Mutant NS is partially degraded by rapid ER associated degradation (ERAD), suggesting that it is targeted for degradation shortly after synthesis, but can also become trapped within long-lived polymers [8,[10][11][12][13].…”
mentioning
confidence: 99%